2019
DOI: 10.1073/pnas.1911007116
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Siglec-1 expression confers susceptibility to HIV-1 infection of human dendritic cell precursors

Abstract: The human dendritic cell (DC) lineage has recently been unraveled by high-dimensional mapping, revealing the existence of a discrete new population of blood circulating DC precursors (pre-DCs). Whether this new DC population possesses specific functional features as compared to the other blood DC subset upon pathogen encounter remained to be evaluated. A unique feature of pre-DCs among blood DCs is their constitutive expression of the viral adhesion receptor Siglec-1. Here, we show that pre-DCs, but not other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 51 publications
2
36
0
1
Order By: Relevance
“…Viral sensing enhances Siglec-1 expression on APCs, and this facilitates HIV-1 infection of DCs and other myeloid cells (Figure 2A, top), such as macrophages [81]. Although DCs are generally resistant to HIV-1 infection, a recent study showed that Siglec-1 mediated HIV-1 productive infection of a population of human DC precursors known as pre-DCs [82]. Even though all DCs express the HIV-1-interacting cellular receptor CD4 and the viral coreceptors [83,84], being therefore susceptible to viral infection in vitro [85][86][87], infectivity was less prominent than in activated CD4 + T cells [88][89][90][91].…”
Section: The Role Of Siglec-1 In DC Infection and Antigen Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral sensing enhances Siglec-1 expression on APCs, and this facilitates HIV-1 infection of DCs and other myeloid cells (Figure 2A, top), such as macrophages [81]. Although DCs are generally resistant to HIV-1 infection, a recent study showed that Siglec-1 mediated HIV-1 productive infection of a population of human DC precursors known as pre-DCs [82]. Even though all DCs express the HIV-1-interacting cellular receptor CD4 and the viral coreceptors [83,84], being therefore susceptible to viral infection in vitro [85][86][87], infectivity was less prominent than in activated CD4 + T cells [88][89][90][91].…”
Section: The Role Of Siglec-1 In DC Infection and Antigen Presentationmentioning
confidence: 99%
“…Thus, trapped viruses are efficiently transmitted across infectious synapses to susceptible lymphocytes [9,132,133] ( Figure 3). This mechanism of viral transmission is known as trans-infection [134] and is mediated by Siglec-1 on activated monocyte-derived DCs, monocytes, blood conventional DCs, pre-DCs, and primary myeloid cells isolated from lymphoid and cervical tissues [38][39][40]56,63,82].…”
Section: Siglec-1 Expression On Different Anatomical Compartments Andmentioning
confidence: 99%
“…In human peripheral blood myeloid cells (including MCs and DCs), known to promote antigen presentation and inflammatory activities, we identified seven transcriptionally distinct subsets: (Fig. S3N), and dendritic cell precursors (pre-DCs) expressing AXL and CD123 (Grabiec and Hussell, 2016;Ruffin et al, 2019) (Fig. S3N).…”
Section: Dissection Of Immune Cell Subtypes In the Cellular Aging Ecomentioning
confidence: 99%
“…In the present study, elevated levels of CD147 on iMonos and ncMonos was a general feature of all patients, while increased levels of CD147 on pDCs, pre-DCs and pre-DC2s were specific to severe COVID-19. In this context it is interesting to note that DC progenitors can themselves be susceptible to viral insult 50 . It remains to be addressed what causes CD147 upregulation in COVID-19 and how the MNP system may participate in dysregulated coagulation, but it has previously been shown that CD147 support platelet-monocyte interactions promoting vascular inflammation 51 .…”
Section: Independent Assessment Of the Mnp Landscape Identifies Clinimentioning
confidence: 99%